Subimperialismo e política externa no Brasil - 2003-2010 - Oliveira, Cesar Augusto de (2017)
This work examinates the concepto of subimperialism, proposed by Ruy Mauro Marini in the 1960‟s, as a category to explain the dynamics of brazilian national capital and its relation towards the dominant imperialism. Considering the fundamental dimensions of the concept, a historic review of Brasil and United States relations is made, and also an operationalization of the north-american strategy for Latin America. Thus, going through the key points on Lula‟s (2003-2010) foreign policy agenda, the application of Marini category‟s in today‟s world can be discussed. Through the analysis of brazilian‟s initiatives in the matters of regional integration, economy and military strategy, it seeks to understand if the politics conducted by Brazil under Lula‟s administration keep expansionist characteristics and if they serve to the interest of the great capital, and at the same time contribute to the reproduction of the capitalist system.